Chemical control of competing electron transfer pathways in iron tetracyano-polypyridyl photosensitizers. Issue 17 (23rd April 2020) - Kunnus, Kristjan; Li, Lin; Titus, Charles J.; Lee, Sang Jun; Reinhard, Marco E.; Koroidov, Sergey; Kjær, Kasper S.; Hong, Kiryong; Ledbetter, Kathryn; Doriese, William B.; O'Neil, Galen C.; Swetz, Daniel S.; et al.
Abstract : Photoinduced intramolecular electron transfer in Fe tetracyano-polypyridyl complexes was investigated with static and time-resolved UV-visible absorption and resonant inelastic X-ray scattering which revealed a competition of two relaxation pathways. Abstract : Photoinduced intramolecular electron transfer dynamics following metal-to-ligand charge-transfer (MLCT) excitation of [Fe(CN)4 (2, 2′-bipyridine)] 2− (1 ), [Fe(CN)4 (2, 3-bis(2-pyridyl)pyrazine)] 2− (2 ) and [Fe(CN)4 (2, 2′-bipyrimidine)] 2− (3 ) were investigated in various solvents with static and time-resolved UV-Visible absorption spectroscopy and Fe 2p3d resonant inelastic X-ray scattering (RIXS). This series of polypyridyl ligands, combined with the strong solvatochromism of the complexes, enables the 1 MLCT vertical energy to be varied from 1.64 eV to 2.64 eV and the 3 MLCT lifetime to range from 180 fs to 67 ps. The 3 MLCT lifetimes in 1 and 2 decrease exponentially as the MLCT energy increases, consistent with electron transfer to the lowest energy triplet metal-centred ( 3 MC) excited state, as established by the Tanabe–Sugano analysis of the Fe 2p3d RIXS data. In contrast, the 3 MLCT lifetime in 3 changes non-monotonically with MLCT energy, exhibiting a maximum. This qualitatively distinct behaviour results from a competing 3 MLCT → ground state (GS) electron transfer pathway that exhibits energy gap law behaviour. The 3 MLCT → GS pathway involves nuclear tunnelling for the high-frequency polypyridyl breathing mode ( hν = 1530 cm −1 ), which is most displaced for complex 3, making this pathway significantly more efficient. Our study demonstrates that the excited state relaxation mechanism of Fe polypyridyl photosensitizers can be readily tuned by ligand and solvent environment. Furthermore, our study reveals that extending charge transfer lifetimes requires control of the relative energies of the 3 MLCT and the 3 MC states and suppression of the intramolecular distortion of the acceptor ligand in the 3 MLCT excited state.